2017
DOI: 10.4102/phcfm.v9i1.1212
|View full text |Cite
|
Sign up to set email alerts
|

Rural-origin health professional students’ perceptions of a support programme offered by Umthombo Youth Development Foundation

Abstract: BackgroundStaffing of rural healthcare facilities is a challenge, with literature supporting the selection and training of rural-origin students. The Umthombo Youth Development Foundation (UYDF) scholarship scheme supports rural students to train as healthcare professionals and offers a unique support programme. This programme has not been evaluated, and this study sought UYDF-supported students’ perceptions of the programme.AimThe aim of the study was to assess students’ perceptions of the UYDF support progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The rural hospitals now have optometrists, radiographers, dieticians, and audiologistsprofessions which were previously only found only in urban areas. [25,26,27] The UYDF graduates have the advantage of knowing the area well and understanding the language, which makes them better able to communicate with patients [28,13] , and to take on outreach work. The health professionals believed that more lives were being saved in hospitals where the UYDF scheme operated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rural hospitals now have optometrists, radiographers, dieticians, and audiologistsprofessions which were previously only found only in urban areas. [25,26,27] The UYDF graduates have the advantage of knowing the area well and understanding the language, which makes them better able to communicate with patients [28,13] , and to take on outreach work. The health professionals believed that more lives were being saved in hospitals where the UYDF scheme operated.…”
Section: Discussionmentioning
confidence: 99%
“…[23] The UYDF believes that providing compulsory mentorship will bridge the gap of poor schooling and equip them with the necessary skills to cope with the demands of Institutions of Higher Learning and health science training. 13 Home Away from Home The students develop a close relationship with the UYDF. Participants stated that they feel cared for, as all their needs were taken care of by the UYDF.…”
Section: Health Science Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scheme started by supporting four (n = 4) students and currently supports around 25o students per annum, studying across 16 health disciplines. To date, 336 students supported by UYDF have graduated in various health science disciplines since initiation of the scheme [9,10]. The UYDF education and training process involves an integrated model of recruitment at school level, selection, support during education and training, employment, support and retention on return to the local rural workplace (table 1).…”
Section: The Uydf Scholarship Schemementioning
confidence: 99%
“…Numerous studies have identified rural origin students as more likely to return to work in rural areas where they originated from [9,10,11]. However widespread poverty, particularly in rural areas of South African has made it difficult to identify rural origin students who can succeed in obtaining a health-related qualification at an institution of higher learning.…”
Section: Introductionmentioning
confidence: 99%